Climate-driven physiological changes in Mahseer (Tor tambroides) juveniles - Nur Syuhada Iskandar; Noorashikin Md Noor; Zaidi Che Cob; Simon Kumar Das; Mohamad Amir Aiman Abdullah (Scientific Reports)
Abstract Climate change, characterized by rising atmospheric carbon dioxide (CO2) levels and increasing global temperatures, poses significant threats to aquatic ecosystems. This study examines the impact of elevated CO2 concentrations and water temperature on the growth, survival, and hematological condition of mahseer juveniles. A controlled experiment was conducted to analyze growth parameters, including specific growth rate (SGR), relative growth rate (RGR), feed conversion ratio (FCR), and hematological indices across varying CO2 and temperature conditions. The findings indicate that CO2 levels significantly influence fish weight, with higher concentrations promoting growth up to a threshold. Elevated temperature negatively affects fish weight gain, particularly at extreme levels. Hematological responses suggest that prolonged exposure to high CO2 and temperature alters blood parameters, indicating physiological stress. The interaction between CO2 and temperature suggests that optimal growth occurs at high CO2 and moderate temperatures, whereas excessive warming exacerbates metabolic stress and mortality. These results provide essential insights for sustainable aquaculture practices and conservation strategies in the face of climate change. The significance of these findings extends to aquaculture industries aiming to optimize fish production under changing environmental conditions.